Comparison of Landfill Leachate Properties by LPI and Phytotoxicity-A Case Study - Wdowczyk, Aleksandra; Szymańska-Pulikowska, Agata (Frontiers in Environmental Science, 2021)
The formation of leachate is one of the inevitable consequences associated with the operation of landfills. In addition to the study of physicochemical composition, toxicity is an important parameter taken into account, among others because of the need to subject leachate to treatment before discharge into the environment. The aim of this study was to determine the degree of leachate contamination using LPI and toxicity index. An analysis of the relationship between the toxic effect on plants and the calculated LPI values was also carried out to assess whether they could provide a measure of leachate toxicity when selecting a treatment method. The research conducted was to determine the degree of leachate contamination using LPI and toxicity index. An analysis of the relationship between the toxic effect on plants and the calculated LPI values was also carried out to assess whether they could provide a measure of leachate toxicity when selecting a treatment method. Calculated values of the leachate pollution index showed that leachates from selected Polish landfills are characterized by low and medium levels of LPI values. The variation in index values obtained was particularly evident between active and closed landfills and was related to the physicochemical composition of leachates. In closed landfills this value ranged from 7.4 to 11.1, while in active landfills from 12.9 to 15.9. The variation in index values obtained was particularly evident between active and inactive landfills and was related to the physicochemical composition of leachates. Phytotoxicity tests showed that leachate at low concentrations can promote plant growth. At higher concentrations (50% and 100%), leachates caused inhibition of root and shoot growth, which correlated with high LPI values. The results confirmed the relationship between the toxic effect on plants and the LPI values, so it can be considered as a reliable indicator of leachate toxicity.